Optimalisasi Budidaya Talas Pratama 3 melalui Demonstration Plot untuk Peningkatan Produktivitas Petani di Kelurahan Situ Gede, Kota Bogor - Sherly Eka Maulidiya; Edi Santosa; Handian Purwawangsa; Mohammad Iqbal Irfany; Danang Aria Nugroho; Ranti Wiliasih; Ahmad Fadli Alghifari; Muhammad Afif Fathin Ridho; Desvita Resti Faniqotuni'mah (Institut Pertanian Bogor, 2026)
The Pratama 3 Taro cultivation optimization program was implemented through a demonstration plot (demplot) approach as a technology-transfer method to increase farmers' capacity in Situ Gede Village, Bogor City. This activity involved 16 farmers from the Saluyu Adult Farmers Group (KTD) and the Geulis Women Farmers Group (KWT) as partners. The implementation method consisted of three main stages, namely land preparation and cultivation demonstration plots, Good Agricultural Practices (GAP) training, and periodic mentoring and monitoring. Data were collected through observation, interviews, and surveys using questionnaires, then analyzed descriptively and quantitatively. The results of the demonstration plot implementation showed an increase in vegetative growth of taro plants up to the 14th WAP phase with an average tuber weight of 1,335 g and productivity reaching 26.7 tons per hectare. Regarding changes in farmer capacity, 93.75% of participants reported increased knowledge, 62.5% reported changes in cultivation techniques, and 68.75% reported increased harvest yields of ≥30%. In addition, product prices increased, and market access improved after the program intervention. These findings indicate that demonstration plots as a participatory learning medium are effective in encouraging technology adoption and increasing the productivity of Talas Pratama 3. This program has the potential to be implemented more widely with further support for post-harvest and marketing aspects to enhance farmers' economic sustainability.